INVENTARISASI NEPENTHES DI TAPANULI SELATAN - Ginting, Nurmaini; Lubis, Jalilah Azizah (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2017)
Research that has been done in 8 districts in South Tapanuli Regency, found 13 types of where 1 of them are natural hybrid. Location Selection is done by the survey method, while sampling in the field using the exploration method. The district has the highest diversity of species is Saipar Dolok Sub-Hole. N. reinwardtiana has the most widely spread. District with the number of the lowest type is East Angkola sub sub-Arse, Marancar Sub-district and sub-district of Tano Tombangan with 1 types.